Advanced Educational Technology: Research Issues and Future Potential
VIII, 219 p.
Keywords: As we approach the 21st century, the need to better link research findings and practical applications of advanced educational technologies (AET) continues to be a priority. During the five-year NATO Special Programme on AET, many advanced study institutes and research workshops focused on building bridges between researchers in and users of educational technology. The organizing committee of the final capstone workshop which took place in September 1993 also chose to focus on this theme. Three position papers, written by members of the AET advisory committee, provided the background and platform for the two-day workshop that was designed to provide guidelines for future AET research and implementation projects. Nicolas Balacheff kicked off the workshop with a philosophical review of the research issues and future research agendas. Herman Bouma and his colleagues at the Institute for Perception Research discussed implementation issues and problems of technology transfer from research laboratories to educational product development.